2001
DOI: 10.1007/s004390100605
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure of karyopherin ?2 ( KPNA2 ) within a low-copy repeat on chromosome 17q23-q24 and mutation analysis in patients with Russell-Silver syndrome

Abstract: Human karyopherin alpha2 (KPNA2), a member of the karyopherin alpha family, plays a key role in the nuclear import of proteins with a classical nuclear localization signal (NLS). KPNA2, as part of a karyopherin alpha-beta heterodimer, directly binds to the NLS of proteins and functions as an adaptor that binds NLS-containing proteins via karyopherin beta to the nuclear pore complex. The NLS protein-receptor complex is translocated through the pore by an energy-dependent mechanism. Recently, we have identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Several studies indicated that KPNA2 extensive expression in breast cancer patients was associated with a short overall patient survival and recurrence-free survival [20], [28], and may warrant consideration as a potential marker for chemoresistance in advanced breast cancer [24]. Our study indicated that KPNA2 extensive expression strongly associates with poor prognosis and recurrence rates of OMGCT patients, as consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies indicated that KPNA2 extensive expression in breast cancer patients was associated with a short overall patient survival and recurrence-free survival [20], [28], and may warrant consideration as a potential marker for chemoresistance in advanced breast cancer [24]. Our study indicated that KPNA2 extensive expression strongly associates with poor prognosis and recurrence rates of OMGCT patients, as consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…KPNA2 has been known to play an important role in regulating epidermal proliferation and differentiation, and activating cellular signaling in blood lymphocytes [17], [27]. KPNA2 has also been associated with the Russell-Silver syndrome [28] and possess tumorigenic activity [18], [29]. A series of reports suggest that KPNA2 expression is linked to breast carcinogenesis and acts as a potential prognostic marker for breast carcinomas [20][23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the translocation breakage has affected KPNA2 involved in the nuclear transport of proteins [46][48]. Thus, KPNA2 has been regarded as a candidate gene for SRS, although mutation analysis of KPNA2 has failed to detect a disease-causing mutation in SRS patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Dörr et al (2001) identified the karyopherin a2 (KNA2) gene in 17q23-q24; however, they excluded this positional candidate gene as relevant to the etiology of SRS. Furthermore, the identification of a SRS patient with a hemizygous deletion of the CSH1 gene in 17q24-q25 (Eggermann et al, 1998) raises the question of the frequency and the significance of this genomic alteration in the disease.…”
Section: Discussionmentioning
confidence: 98%